Predictors of 6 Month Health Utility Outcomes in Survivors of Acute Respiratory Distress Syndrome - Brown, Samuel M. (Thorax, 2016)
BACKGROUND: With improving short-term mortality in Acute Respiratory Distress Syndrome (ARDS), understanding and improving quality of life (QOL) outcomes in ARDS survivors is a clinical and research priority. We sought to identify variables associated with QOL, as measured by the EQ-5D health utility score, after ARDS using contemporary data science methods. METHODS: Analysis of prospectively acquired baseline variables and 6-month EQ-5D health utility scores for adults with ARDS enrolled in the ARDS Network Long-Term Outcome Study (ALTOS). Penalized regression identified predictors of health utility, with results validated using 10-fold cross-validation. RESULTS: Among 616 ARDS survivors, several predictors were associated with 6-month EQ-5D utility scores, including two lifestyle factors. Specifically, older age, female sex, Hispanic/Latino ethnicity, current smoking, and higher body mass index (BMI) were associated with lower EQ-5D utilities, while living at home without assistance at baseline and AIDS were associated with higher EQ-5D utilities in ARDS survivors. No acute illness variables were associated with EQ-5D utility. CONCLUSIONS: Acute illness variables do not appear to be associated with post-discharge QOL among ARDS survivors. Functional independence and lifestyle factors, such as obesity and tobacco smoking, were associated with worse QOL. Future analyses of post-discharge health utility among ARDS survivors should incorporate measures of demographics and functional independence at baseline.